Developing An-Intelligent System as Reference for Food-Drug Interactions and Chronic Disease Management in The Arab Community - Al_Radi Amal A. et al. (University of Science and Technology, Sana'a, Faculty of Medicine and Health Sciences, Nutrition Program, 2025)
This research aims to address this issue by designing and developing an intelligent and integrated technological system called "Nutridrug Interact." This system serves as a supportive and educational tool for patients with chronic diseases, combining accurate medical information with the power of modern technology. The study adopted an applied approach, building a reliable medical database containing 50 chronic diseases and their commonly used medications, based on standardized global sources (such as the World Health Organization (WHO) and the UK's National Health Service (NHS)). Technically, the application was developed using the Flutter framework and a clean architecture, adopting an innovative hybrid model. The application's core references and nutritional alert system rely on a high-speed local database (Isar Database) to ensure instant access to information without requiring an internet connection. In a pioneering move, generative AI technologies were integrated via the Google Gemini 3 Pro model to create an intelligent health assistant ("guide") with multimodality capabilities. This allows it to analyze and recognize images of medications taken by the patient and accurately detect potential interactions, all within strict safety protocols that prevent medical diagnosis and focus on education and guidance.